Preferência de Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) por lagartas de Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) alimentadas com diferentes cultivares de cana-de-açúcar - Souza, Joseane Rodrigues De; Boiça Júnior, Arlindo Leal [UNESP]; Perecin, Dilermando [UNESP]; Costa, Jacqueline Tonielo Da [UNESP]; Peixoto, Marília Lara [UNESP] (Universidade Federal de Viçosa, 2014)
The objective of this study was to evaluate the preference of the parasitoid C. flavipes (Hymenoptera: Braconidae) for larvae of Diatraea saccharalis (Lepidoptera: Crambidae) fed on different sugarcane cultivars. The experiments were conducted in laboratory with two feeding conditions: larvae of D. saccharalis fed on artificial diet and larvae fed on artificial diet and kept temporarily on cane setts of the different cultivars. The resistant cultivars SP80-1842 and SP81-3250and the susceptible RB855536 cultivar to D. saccharalis were used in the experiment. The oviposition preference of C. flavipes females was evaluated in free-choice and no-choice tests, in a completely randomized design with four treatments and 15 replications. Larvae of D. saccharalis with 19 days of age were fed to mated females of C. flavipes with 24 hours of age in both tests.. For the free-choice test was used an olfactometer of four compartments, in which four females of C. flavipes were released in its center. For the no-choise test was used Petri dishes, each one with one larva of D. saccharalis treated under both feeding conditions. In these tests, it was determined the percentage of parasitism and continuously observed the behavior of the first choice of C. flavipes females at intervals of zero to one; one to three, three to five, five to eight and eight to ten minutes. Larvae of D. saccharalis reared in artificial diet with powdered stems of the cultivars were equaly preferred by females of the parasitoid C. flavipes; The percentage of parasitism of D. saccharalis larvae reared on artificial diets with powdered stems of the cultivars SP80-1042 and RB855536 were equaly parasitized by C. flavipes.

O objetivo desta pesquisa foi avaliar a preferência do parasitoide Cotesia flavipes (Hymenoptera: Braconidae) por lagartas de Diatraea saccharalis (Lepidoptera: Crambidae), alimentadas com diferentes cultivares de cana-de-açúcar. O experimento foi conduzido em laboratório, em duas condições de alimentação, uma envolvendo lagartas de D. saccharalis, alimentadas em dieta artificial, e, a outra, com lagartas alimentadas em dieta artificial e mantidas temporariamente nos toletes dos cultivares de cana-de-açúcar. Os cultivares utilizados foram: SP80-1842 e SP81-3250, resistentes, e RB855536, suscetível à D. saccharalis. A preferência para oviposição das fêmeas de C. flavipes foi avaliada em testes com e sem chance de escolha, em delineamento inteiramente casualizado, com quatro tratamentos e 15 repetições. Lagartas de D. saccharalis com 19 dias de idade foram oferecidas para fêmeas de C. flavipes, acasaladas e com 24 horas de idade, em ambos os testes. No teste com chance de escolha, utilizou-se um olfatômetro, o qual constou de quatro compartimentos, em cujo centro liberaram-se quatro fêmeas de C. flavipes, enquanto, no teste sem chance de escolha, foram utilizadas placas de Petri, no interior das quais se colocou uma lagarta de D. saccharalis, oriunda das duas condições de alimentação. Nestes testes, foi observada a percentagem de parasitismo e, continua-mente, o comportamento da primeira escolha de fêmeas de C. flavipes, em intervalos de zero a um, um a três, três a cinco, cinco a oito e de oito a dez minutos após as liberações. Lagartas de D. saccharalis, oriundas da alimentação em dieta artificial com colmos triturados dos cultivares, foram igualmente preferidas para atratividade de fêmeas do parasitoide C. flavipes. A percentagem de parasitismo de lagartas de D. saccharalis, criadas com dietas artificiais com colmos dos cultivares SP80-1042 e RB855536, foi igualmente parasitadas por C. flavipes.
Preference of Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) for larvae of Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) fed on different sugarcane cultivars
Keywords: Saccharum spp.; extrinsic resistance; sugarcane borer; biological control; parasitoid; Saccharum spp.; resistência extrínseca; broca-da-cana; controle biológico; parasitoide